Helicobacter pylori Eradication and Gastric Cancer Prevention - Chan Hyuk Park (Yong Chan Lee, 2021)
Since Warren and Marshall demonstrated Helicobacter pylori (H. pylori) as a cause of gastritis in the early 1980s, H. pylori has been associated with various gastric diseases, including gastric ulcer, gastric mucosa-associated lymphoid tissue (MALT) lymphoma, gastric adenoma, gastric adenocarcinoma, and hyperplastic gastric polyps. H. pylori eradication therapy can treat some associated diseases, including low-grade gastric MALT lymphoma, and significantly reduce the risk of peptic ulcer recurrence or progression of atrophic gastritis and intestinal metaplasia. In East Asia, where H. pylori and gastric cancer are prevalent, several studies have been conducted to prove whether the risk of gastric cancer development is reduced through H. pylori eradication therapy. Early studies failed to show the benefits of H. pylori eradication therapy in gastric cancer prevention. However, recent studies with extended follow-up periods have reported reduced risks of gastric cancer after treatment of H. pylori infection. H. pylori eradication therapy effectively prevents gastric cancer even in patients who were treated for early gastric cancer, and can be used in treating hyperplastic gastric polyps. Herein, we reviewed current evidence supporting the benefits of H. pylori eradication therapy to help clinicians understand its impact on gastric cancer prevention and hyperplastic polyp treatment.